Sistem Pendukung Keputusan Pemilihan Anggota Pengurus Harian Pondok Pesantren Menggunakan Metode Profile Matching (Studi Kasus Pondok Pesantren Putra Sabilurrosyad) - Muhammad Atabik Usman; Edy Santoso; Nurul Hidayat (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Nowadays, computerization has often been a daily necessary which aims to facilitate our activity in all time. In order that, there were many problems which could be overcome by using the calculation in computerizing. For example, in term of organization, that is to elect the candidate of daily manager Putra Sabilurrosyad Islamic Boarding School which still possess obstacles, both in human source and time that were running out the time to elect the candidate of daily manager in Putra Sabilurrosyad Islamic Boarding School. In this study, the system will produce the software application that named the decision support system maker, which is to elect the candidate of daily manager in Putra Sabilurrosyad Islamic Boarding School. The result from this paper is the rating which is from the pupils who have been qualified, the output that was from the application provided and assisted in decision makers electing the pupils who will be the member of daily manager in Putra Sabilurrosyad Islamic Boarding School. The application implements using web based program. The result of this research using this profile matching method get the percentage of 97% accuracy level.